What Drives Global Lending Syndication? Effects of Cross-Country Capital Regulation Gaps. (28th July 2020) - Gao, Janet; Jang, Yeejin
Abstract: We examine how cross-country differences in capital regulations shape the structure of global lending syndicates. Using globally syndicated loans extended by banks from forty-four countries, we find that strictly regulated banks participate more in syndicates originated by lead lenders facing less stringent capital regulations. The resulting lending syndicates extend loans to riskier borrowers, charge higher spreads, forego covenants more frequently, and incur higher default rates. Such syndication activity also facilitates the access to credit by riskier corporations and exposes both participants and lead arrangers to greater systemic risk. Overall, our finding is consistent with the explanation that strictly regulated banks rely on the expertise of loosely regulated banks to procure risky deals outside the border.